In-band full duplex wireless communications - Chen, Yulin (2017)
Nowadays, wireless communication has been widely used in our life. As one of the results, the radio frequency spectrum resource becomes less and less. In Band Full-Duplex has a great potential to improve the efficiency of the RF spectrum and is developing by the worldwide research team. In Band Full-Duplex transmits uplink and downlink signal in the same frequency band and at the same time. It can not only improve the spectrum efficiency not also shorter the latency. However, In Band Full-Duplex also create a major problem which is the strength self-interference. The goal of this project is to evaluate the self-interference cancellation techniques.